2016
DOI: 10.3171/2016.1.spine15891
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of recombinant human bone morphogenetic protein-2 on pain-associated behaviors in a rat model following implantation near the sciatic nerve

Abstract: OBJECTIVE It has been hypothesized that the recombinant human bone morphogenetic protein-2 (rhBMP-2) amplification of the host inflammatory response interacts with nerves in the spine and contributes to the occurrence of new, postoperative complaints of radiculitis. This in vivo rat study was conducted to assess the capacity for rhBMP-2/ACS (rhBMP-2 applied to absorbable collagen sponge [ACS]) to stimulate pain-associated behaviors in the rat chronic constriction inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Therefore a generalized rapid increased inflammatory environment surrounding the DRG neurons after rhBMP-2/ACS implantation could explain the transient increase in thermal and mechanical sensitivity we found. Our data are in contrast to those of Zanella et al [41] who find no direct effect of either rhBMP-2/ACS or ACS alone on the thermal hypersensitivity that results after direct application to the sciatic nerve in the chronic constriction injury (CCI) neuropathic pain model. However, the CCI model causes significant inflammation by itself [42], so it is not clear whether additional inflammatory stimuli would further increase the large nociceptive changes seen in this model.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore a generalized rapid increased inflammatory environment surrounding the DRG neurons after rhBMP-2/ACS implantation could explain the transient increase in thermal and mechanical sensitivity we found. Our data are in contrast to those of Zanella et al [41] who find no direct effect of either rhBMP-2/ACS or ACS alone on the thermal hypersensitivity that results after direct application to the sciatic nerve in the chronic constriction injury (CCI) neuropathic pain model. However, the CCI model causes significant inflammation by itself [42], so it is not clear whether additional inflammatory stimuli would further increase the large nociceptive changes seen in this model.…”
Section: Discussioncontrasting
confidence: 99%
“…[53][54][55][56] Notably, a recent study 57 found that implantation of rhBMP2-soaked absorbable collagen sponges (ACS) at the dorsal root ganglion triggered potent neuroinflammatory response, along with a transient change in thermal and mechanical sensitivity in rats. In contrast, another study 58 reported that rhBMP2-ACS application had a neuroprotective effect and decreased pain behavior in a rat NP model of CCI. Thus, BMP2 may have complicated role in the regulation of NP.…”
Section: The Antagonistic Effect Of Noggin On Bmp4-induced Allodynia and Astrocyte Activationmentioning
confidence: 81%